2018
DOI: 10.1523/jneurosci.3542-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Triggers Peripheral Macrophage-to-Sensory Neuron Redox Crosstalk to Elicit Pain

Abstract: Injury, inflammation, and nerve damage initiate a wide variety of cellular and molecular processes that culminate in hyperexcitation of sensory nerves, which underlies chronic inflammatory and neuropathic pain. Using behavioral readouts of pain hypersensitivity induced by angiotensin II (Ang II) injection into mouse hindpaws, our study shows that activation of the type 2 Ang II receptor (AT2R) and the cell-damage-sensing ion channel TRPA1 are required for peripheral mechanical pain sensitization induced by Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 88 publications
7
120
1
Order By: Relevance
“…Additionally, recent evidence shows that macrophages express AT2R which upon activation by Ang‐II release reactive oxygen/nitrogen species. These alter the function of TRPA1 receptors in sensory neurons (Shepherd et al ). Thus, macrophages recruited early during cutaneous inflammation may contribute to inflammatory pain via potentiation of the local renin–angiotensin system and also by sensitizing TRPA1 + terminals.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent evidence shows that macrophages express AT2R which upon activation by Ang‐II release reactive oxygen/nitrogen species. These alter the function of TRPA1 receptors in sensory neurons (Shepherd et al ). Thus, macrophages recruited early during cutaneous inflammation may contribute to inflammatory pain via potentiation of the local renin–angiotensin system and also by sensitizing TRPA1 + terminals.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting observation emerging from our work is that some macrophages are apparently present in DRG cultures and this macrophage phenotype is inflammatory in nature. An emerging literature describes DRG resident macrophages as key players in development of many chronic pain states, including neuropathic pain [23; 27; 39; 51; 61]. In future studies it may be possible to manipulate these macrophages to interact with DRG neurons in culture to push this neuropathic pain phenotype further toward the generation of spontaneous activity.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, investigators have studied rodent nociceptors in vitro as dissociated cell cultures prepared from DRG or TG. More recently, investigators have also started to study DRG nociceptors from human organ donors and surgical patients [14; 39; 47; 50; 51; 59; 70]. This creates a “clinical bridge” for advancing mechanisms or therapeutics from rodents toward the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…administration of Ang II causes hypersensitivity (Shepherd, Copits, et al, ). While it was suggested that the induction of neuropathic pain involves the activation of AT2 receptors in DRGs (Smith et al, ), other reports indicate that it involves AT2 receptors on peripheral macrophages (Shepherd, Copits, et al, ; Shepherd, Mickle, et al, ). As the action site of Ang II is still debated and requires further studies, we have investigated pain transmission from the perspective of the spinal Ang system.…”
Section: Discussionmentioning
confidence: 99%